Common surgery, uncommon complication - Hande Akdeniz; Kadri Ozer; Adile Dikmen; Ugur Kocer (Mattioli1885, 2015)
Ingrown nail surgery is the one of the most common surgeries in outpatient clinics that are generally perfomed in response to patient complaints. Still, making simple observations, taking patient histories and conducting further tests are often neglected by outpatient clinics. Consequently, it is important to be aware if ingrown nail is associated with any underlying diseases that can lead to major complications. In this article, we report on two cases ending in amputation that were performed with Winograd's partial matrix excision procedure for ingrown nails. Such a complication is rare, unexpected, and most unwanted in forefoot surgery. After a detailed analysis of the situation, we discovered that both patients were smokers, and one of them had Buerger's disease. These conditions led to the ingrown nails in addition to poor wound healing. This case report emphasizes the fact that even when performing minor procedures, obtaining a detailed history and conducting an examination are of paramount importance. Patient selection is also a considerable factor, especially for patients who are smokers, who may experience a worst case surgical scenario.